Implementasi Sistem Pencarian Perangkat USB berbasis Protokol USB/IP dalam Jaringan IP Multicast - La Ode Muh. Fadlun Akbar; Dahnial Syauqy; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
USB/IP is a technology that proposes a USB device sharing mechanism has some problems related to their access mechanisms. The problem is there are no service discovery system that makes USB device sharing mechanism is inefficient. This causes the user has to know exactly the IP address of USB/IP provider and through a highly technical configuration process. The problem can be solved by implementing a service discovery system to USB/IP protocol by utilizing group management system in the IP multicast network. Not only resolved IP address problems, we also provide limits on the scope of USB/IP services when it operates. In this research, there are 4 important components to realize the discovery system, there are limitation of scope, communication method, system observation method, and method of selecting and requesting access of USB device. Based on implementation, updating the list of USB devices (based on system observation method) takes the longest time among other mechanisms, which is 569,033Â±6,036 milliseconds. This is due to sequence of processes that need to be run, both on the USB/IP provider as well as on the user application. Moreover, the service discovery system can be implemented without changing the original specifications of USB/IP.